2010
DOI: 10.1039/c0cp00578a
|View full text |Cite
|
Sign up to set email alerts
|

High resolution Dopplerimetry of correlated angular and quantum state-resolved CO2 scattering dynamics at the gas–liquid interface

Abstract: Full three dimensional (3D) translational distributions for quantum state-resolved scattering dynamics at the gas-liquid interface are presented for experimental and theoretical studies of CO(2) + perfluorinated surfaces. Experimentally, high resolution absorption profiles are measured as a function of incident (θ(inc)) and scattering (θ(scat)) angles for CO(2) that has been scattered from a 300 K perfluorinated polyether surface (PFPE) with an incident energy of E(inc) = 10.6(8) kcal mol(-1). Line shape analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…It is important to emphasize that high levels of 1:1 imaging/spatial filtering in the LIF detection have been implemented to eliminate contributions of incident cold beam contamination to the populations extracted. This behavior would at first seem entirely consistent with “bifurcation” into trapping desorption (TD) and impulsive scattering (IS) pathways, which have been routinely identified in gas–liquid scattering studies via time-of-flight analysis of translations, , as well as for internal rotational degrees of freedom in quantum-state-resolved studies. ,,− In particular, the lower temperature TD component in such studies often (but not always) reflects complete equilibration with the surface, with the higher temperature IS component responsible for capturing any dynamical (nonequilibrium) contributions to the scattering event. In the context of this standard TD/IS model, one might anticipate the lower temperature to match the surface ( T low ≈ T S ≈ 873 K), with a second “temperature” component hotter than the surface ( T high > T S ) and increasing with incident energy.…”
Section: Results and Analysissupporting
confidence: 54%
“…It is important to emphasize that high levels of 1:1 imaging/spatial filtering in the LIF detection have been implemented to eliminate contributions of incident cold beam contamination to the populations extracted. This behavior would at first seem entirely consistent with “bifurcation” into trapping desorption (TD) and impulsive scattering (IS) pathways, which have been routinely identified in gas–liquid scattering studies via time-of-flight analysis of translations, , as well as for internal rotational degrees of freedom in quantum-state-resolved studies. ,,− In particular, the lower temperature TD component in such studies often (but not always) reflects complete equilibration with the surface, with the higher temperature IS component responsible for capturing any dynamical (nonequilibrium) contributions to the scattering event. In the context of this standard TD/IS model, one might anticipate the lower temperature to match the surface ( T low ≈ T S ≈ 873 K), with a second “temperature” component hotter than the surface ( T high > T S ) and increasing with incident energy.…”
Section: Results and Analysissupporting
confidence: 54%
“…In general, contributions to this IS channel occur on a much faster time scale (≤1–10 ps). From quantum-state-resolved molecular beam studies at nonorthogonal angles of incidence, this channel often appears as a lobular forward scattering peak with a hot yet remarkably “temperature-like” distribution of internal rotational quantum states. ,, It is worth noting that the dynamical propensity toward such “hyperthermal” rotational distributions in the IS channel is far from obvious and indeed quite surprising, particularly as the translational degrees of freedom for in-plane IS scattering measured from TOF studies are routinely far out of equilibrium. Interestingly, there has been progress in characterizing the dynamical origin of these hot but “Boltzmann-esque” rotational distributions based on sharp rainbow features smoothed by thermal roughness at the gas–liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…There is no a priori reason why the rotational distribution from a direct scattering process should be described by a rotational temperature, but recent experiments studying a range of molecular species with a wide variety of liquid surfaces have shown that this is a very common outcome. 9,[16][17][18][19]21,22,24,[27][28][29][30][31]34,56 The fitted rotational temperature corresponds to a fraction f R = 0.16 ± 0.02 of the available incident kinetic energy being converted from translation to rotation in collisions at the liquid surface. This is broadly comparable to the previous limited measurements of rotationally inelastic scattering of small molecules at PFPE surfaces.…”
Section: ■ Discussionmentioning
confidence: 99%
“…17 In contrast, the scattered speed distributions of both NO and CO 2 from PFPE observed by Nesbitt and co-workers have been successfully interpreted within an IS:TD model with substantial thermal components at the surface temperature, consistent with their associated rotational temperature analysis. 18,19,21,22,24,27,31 The origin of these implied differences in the fraction of the scattered distribution that appears to be surface equilibrated is as yet unknown. Further work is clearly required, including improvements in the signal to noise and an expansion of the present study to include different incident kinetic energies, better-defined initial transverse velocity distributions through skimming of the molecular beam, and introduction of different liquid surfaces, particularly potentially reactive hydrocarbon surfaces such as squalane, C 30 H 62 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation